Load Transfer Law of Anti-Floating Anchor With GFRP Bars Based on Fiber Bragg Grating Sensing Technology - Zhang, Yamei; Bai, Xiaoyu; Yan, Nan; Sang, Songkui; Jing, Desheng; Chen, Xiaoyu; Zhang, Mingyi (Frontiers in Materials, 2022)
Glass Fiber Reinforced Polymer (GFRP) anchor, a new type of composite material anchor, has been widely used in foundation engineering of coastal areas. This study investigated the feasibility of applying fiber Bragg grating (FBG) sensing technology to monitor the strain of the GFRP anchor during pull test. Based on an advanced method, the FBG strain sensors were installed in GFRP anchors during the anchors manufacturing process. The GFRP anchors then were installed into the pre-created borehole with M30 cement mortar. Meanwhile, the FBG temperature sensors were installed next to the GFRP anchors to monitor the temperature change during the test. The axial force and average shear stress of GFRP anchors along depth during pull test were analyzed, and the influence of temperature change on strain measurement was studied. The test results showed that the FBG sensing technology and the installation method of FBG strain sensors used in the test were feasible to monitor the mechanical properties of the GFRP anchor during pull test. Moreover, the effect of temperature change on strain monitoring of FBG strain sensors was negligible.